Increased classical endoplasmic reticulum stress is sufficient to reduce chondrocyte proliferation rate in the growth plate and decrease bone growth. - Louise H W Kung; M Helen Rajpar; Richard Preziosi; Michael D Briggs; Raymond P Boot-Handford (PLoS ONE)
Mutations in genes encoding cartilage oligomeric matrix protein and matrilin-3 cause a spectrum of chondrodysplasias called multiple epiphyseal dysplasia (MED) and pseudoachondroplasia (PSACH). The majority of these diseases feature classical endoplasmic reticulum (ER) stress and activation of the unfolded protein response (UPR) as a result of misfolding of the mutant protein. However, the importance and the pathological contribution of ER stress in the disease pathogenesis are unknown. The aim of this study was to investigate the generic role of ER stress and the UPR in the pathogenesis of these diseases. A transgenic mouse line (ColIITgcog) was generated using the collagen II promoter to drive expression of an ER stress-inducing protein (Tgcog) in chondrocytes. The skeletal and histological phenotypes of these ColIITgcog mice were characterised. The expression and intracellular retention of Tgcog induced ER stress and activated the UPR as characterised by increased BiP expression, phosphorylation of eIF2α and spliced Xbp1. ColIITgcog mice exhibited decreased long bone growth and decreased chondrocyte proliferation rate. However, there was no disruption of chondrocyte morphology or growth plate architecture and perturbations in apoptosis were not apparent. Our data demonstrate that the targeted induction of ER stress in chondrocytes was sufficient to reduce the rate of bone growth, a key clinical feature associated with MED and PSACH, in the absence of any growth plate dysplasia. This study establishes that classical ER stress is a pathogenic factor that contributes to the disease mechanism of MED and PSACH. However, not all the pathological features of MED and PSACH were recapitulated, suggesting that a combination of intra- and extra-cellular factors are likely to be responsible for the disease pathology as a whole.